Competitive balance and sport spectatorship : an analysis of Singapore professional football - Phua, Philip Yi Xian (2017)
Sports Spectatorship has become a major part of world culture, with large revenues being recorded for many sport teams around the world. However, many sport leagues experience low or declining attendances. As such, there is a need to study variables pertaining to spectatorship to help sport administrators identify what can be done to improve attendances. This paper aimed to investigate the relationship of competitive balance among teams in a sports league with the average attendance of the league itself. The study was conducted on 6 seasons of the Singapore Football League, also known as the S-League. Two within-season measures of competitive balance - the Realised Standard Deviation (RSD) and the Herfindahl-Hirschman Index (HHI) were used for this study, and compared with the average attendance of each season, which were obtained from league publications. The findings suggested that attendances were higher as competitive balance improved. However, the result of a Spearman rank correlation test yielded no significant relationship between average attendance and RSD* (p=0.544), as well as HHI (p=0.623). The inability to obtain significance could have been due to anomalous events that occurred in specific seasons that influenced other variables that outweighed competitive balance. A larger study would need to be conducted over a longer time frame to reduce the impact of such events.